2023
DOI: 10.1186/s13287-023-03351-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization strategies of mesenchymal stem cell-based therapy for acute kidney injury

Abstract: Considering the high prevalence and the lack of targeted pharmacological management of acute kidney injury (AKI), the search for new therapeutic approaches for it is in urgent demand. Mesenchymal stem cells (MSCs) have been increasingly recognized as a promising candidate for the treatment of AKI. However, clinical translation of MSCs-based therapies is hindered due to the poor retention and survival rates as well as the impaired paracrine ability of MSCs post-delivery. To address these issues, a series of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…The mechanism of MSC/ASC-mediated protection is not fully understood. Originally, considered as a source of adult progenitor cells to mediate tissue repair, there are discrepant reports that injected MSCs home to the site of tissue injury [ 11 13 , 34 ]. In our own study, suprarenal injection of ASCs preserved kidney function in the absence of homing [ 15 ], suggesting that the therapeutic effect is mediated by factors liberated from ASC and/or modulation of distant cells or tissues, such as cells comprising the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of MSC/ASC-mediated protection is not fully understood. Originally, considered as a source of adult progenitor cells to mediate tissue repair, there are discrepant reports that injected MSCs home to the site of tissue injury [ 11 13 , 34 ]. In our own study, suprarenal injection of ASCs preserved kidney function in the absence of homing [ 15 ], suggesting that the therapeutic effect is mediated by factors liberated from ASC and/or modulation of distant cells or tissues, such as cells comprising the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…However, low survival rates, low homing rates and ambiguous differentiation limit the therapeutic efficacy of MSCs. To overcome these limitations, various strategies have emerged to enhance the efficacy of stem cells, including drug pretreatment, gene modification, and biomaterial encapsulation [ 7 , 8 ]. Previous studies have shown that pharmacological enhancement of cellular bioactivity and improvement of the microenvironment for cell growth before transplantation is an effective pretreatment strategy for cellular therapy that can greatly benefit tissue repair [ 9 ].…”
Section: Introductionmentioning
confidence: 99%